A tetrameric protein scaffold as a nano-carrier of antitumor peptides for cancer therapy. (June 2019) - Ma, Bohan; Niu, Fan; Qu, Xiaoyan; He, Wangxiao; Feng, Chao; Wang, Simeng; Ouyang, Zhenlin; Yan, Jin; Wen, Yurong; Xu, Dan; Shao, Yongping; Ma, Peter X.; et al.
Abstract: A major pharmacological barrier to peptide therapeutics is their susceptibility to proteolytic degradation and poor membrane permeability, which, in principle, can be overcome by nanoparticle-based delivery technologies. Proteins, by definition, are nano materials and have been clinically proven as an efficient delivery vehicle for small molecule drugs. Here we describe the design of a protein-based peptide drug carrier derived from the tetramerization domain of the chimeric oncogenic protein Bcr/Abl of chronic myeloid leukemia. A dodecameric peptide inhibitor of the p53-MDM2/MDMX interaction, termed PMI, was grafted to the N-terminal helical region of Bcr/Abl tetramer. To antagonize intracellular MDM2/MDMX for p53 activation, we extended this protein, PMI Bcr/Abl, by a C-terminal Arg-repeating hexapeptide to facilitate its cellular uptake. The resultant tetrameric protein PMI Bcr/Abl-R6 adopted an alpha-helical conformation in solution and bound to MDM2 at an affinity of 32 nM. PMI Bcr/Abl-R6 effectively induced apoptosis of HCT116 p53 +/+ cells in vitro in a p53-dependent manner and potently inhibited tumor growth in a nude mouse xenograft model by stabilizing p53 in vivo . Our protein-based delivery strategy thus provides a clinically viable solution to p53-inspired anticancer therapy and is likely applicable to the development of many other peptide therapeutics to target a great variety of intracellular protein-protein interactions responsible for disease initiation and progression.